Studying immunotherapeutic properties of the conjugate based on BCG antigens with betulonic acid in guinea pigs infected with Mycobacterium scrofulaceum - I. N. Koshkin; V. S. Vlasenko; N. A. Dengis (Ветеринария сегодня)
The paper reports on the research into the immunotherapeutic properties of a conjugate based on BCG antigens with betulonic acid after experimental infection of guinea pigs with Mycobacterium scrofulaceum culture, belonging to nontuberculosis mycobacteria type II according to the Runyon classification. Fifteen guinea pigs were used for the experimental purposes, divided into 3 groups. Mycobacterium scrofulaceum was subcutaneously injected into animals of Groups 1 and 2 (n = 10) at a dose of 5 mg. Fourteen days later, a conjugate based on BCG antigens with betulonic acid was subcutaneously injected into animals of Group 2 (n = 5) at a dose of 500 µg/mL of protein. Five intact animals were used as controls. During the experiment, neutrophil bactericidal activity was assessed, and histopathological examination of inguinal lymph nodes was done. The experiment showed that the inoculation of Mycobacterium scrofulaceum into guinea pigs activates cationic proteins and neutrophil myeloperoxidase, and on experiment day 42 (preceded by mycobacteria withdrawal from the body) their concentration reduced to the level of the control group. The vaccine administration induced a more active intracellular phagocyte metabolism during the entire observation period, which resulted in the elimination of nontuberculosis mycobacteria in animals as early as day 7 after treatment with the conjugate. The elimination was confirmed by the absence of mycobacterial antigen in blood smears tested in indirect immunofluorescence, as well as by histopathological changes in inguinal lymph nodes demonstrated as a reduction of germinal centers within lymphoid follicles.